High Level of Inflammatory Cytokines in the Tears: A Bridge of Patients with Concomitant Exotropia and Dry Eye. (7th October 2021) - Gao, Feng; Hong, Xiaoping; Ding, Fadian; Huang, Shirong; Lian, Wei; Wang, Hanjun; Zheng, Weidong; Ni, Jun; Chen, Min; Liu, Qicai
Abstract : Concomitant exotropia have obvious symptoms of eye discomfort in adults, and the presence of ocular surface inflammation in patients may be important mediators between concomitant exotropia and dry eye. Oculus Keratograph eye comprehensive analyzer was performed to detect noninvasive tear break time, noninvasive tear height, and eye red index, while the ocular surface disease index and schirmer I testing were made. The levels of IL-6, IL-10, IL-17A, IL-12P70, INF- γ, and TNF- α were detected in tears in patients with concomitant exotropia and healthy controls matched by age and gender through the Simoa technology. IL-6 was significantly higher in patients with concomitant exotropia (4.683 ± 1.329 ) pg/mL than that in normal group (1.455 ± 0.391 ) pg/mL, p = 0.0304 . TNF- α was also significantly higher in patients (0.2095 ± 0.0703 ) pg/mL than normal group (0.0513 ± 0.0149 ) pg/mL, p = 0.0397 . The levels of inflammatory factors in strabismic patients vs. normal controls were as follows: IL-17A (0.1551 pg/mL︰0.0793 pg/mL), IL-10 (0.3358 pg/mL︰0.0513 pg/mL), IL-12p70 (0.0253 pg/mL︰0.0099 pg/mL), and INF- γ (0.0284 pg/mL︰0.009 pg/mL) were detected, and the median of them in concomitant strabismus was 1.96-6.55-fold as much as the control group. High levels of inflammatory cytokines in tears of patients with concomitant exotropia, which may be a potentially factor promoted the occurrence of dry eye in the patients with concomitant exotropia.